Contingency Based Tourism Village Managerial: Proposed Development of Eco-Village Tourism in Bantul Regency. - Hadi Oetomo; Titik Kusmantini; Hendri Gusaptono; Yekti Utami (Universitas Lambung Mangkurat, 2020)
This research aims to review the theoretical study of contingency theory and the concept of entrepreneurship in the context of submitting research prepositions about antecedent factors and the consequences of management patterns of eco-village tourism. Observations are planned to be carried out using a sample of 11 tourist villages in Bantul Regency and data collection is carried out by in-depth interview techniques with 25 research participants including community leaders, business people and government officials who manage Small and Medium Enterprises (SME). More detailed this paper explores the external and internal environmental factors that have a significant influence on the managerial pattern of eco-friendly tourism villages. Managerial pattern dimensions include the intensity of innovation, pro- active behavior and business agility are also predicted to determine the success of the management of environmentally friendly tourism villages.